2007
DOI: 10.1038/sj.eye.6702772
|View full text |Cite
|
Sign up to set email alerts
|

Ocular disorders in a petroleum industry in Nigeria

Abstract: Objective To determine the ocular disorders in the petroleum industry in Warri, Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
3
15
2
Order By: Relevance
“…This value is much lower than the 56.7% found by Titiyal et al in six industrial establishments at Saharanpur in India in the year 1998 [11] but higher than the selected industrial establishments (cement factory, mining, saw mill and steel works) in Enugu, Nigeria [4] where only 26.2% was found in that study. This does not prove that uncor rected refractive errors can cause eye diseases in factory workers because our data is too small to represent an industrial workforce of 90.1 million in the country [15] and a further survey to be conducted in the future.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This value is much lower than the 56.7% found by Titiyal et al in six industrial establishments at Saharanpur in India in the year 1998 [11] but higher than the selected industrial establishments (cement factory, mining, saw mill and steel works) in Enugu, Nigeria [4] where only 26.2% was found in that study. This does not prove that uncor rected refractive errors can cause eye diseases in factory workers because our data is too small to represent an industrial workforce of 90.1 million in the country [15] and a further survey to be conducted in the future.…”
Section: Discussioncontrasting
confidence: 52%
“…Most of these hazards are preventable if adequate precautionary measures are taken [1][2][3][4]. Worker's eyes may be exposed to a variety of dangerous agents depending on the type of industry which may constitute an occupational hazard [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In support, in a preliminary study based in South Africa, outdoor workers reported painful eyes and blurring of vision during the hottest weather which may indicate ocular sunburn. 7 Conjunctivitis (diagnosed as allergic conjunctivitis) was significantly more common in technical/outdoor workers than in non-technical/indoor workers in the Delta State of Nigeria which lies near the Equator, 9 and thus may represent photoconjunctivitis due to high dose exposure to solar UVR.…”
Section: Photoconjunctivitis and Photokeratitismentioning
confidence: 99%
“…6 Only three studies reported on the acute health effects of sun exposure. [7][8][9] These are considered separately in the following section and are not included in Table 2. There was a notable lack of studies about sun protection practices in Africa.…”
Section: Photochemical and Photobiological Sciencesmentioning
confidence: 99%
See 1 more Smart Citation